2020
DOI: 10.1007/978-3-030-52067-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Electronic Service Quality on Electronic Loyalty in Online Shopping Context: Data Analysis Approach

Abstract: According to News24 [1], online learning tools for instance Cisco System's WebEx Zoom, Instructure's Canvas, and many other educational tech companies across the U.S. reported instant increase by 700% in sales. While, the online booking and travel sites drops by 20.8%, online grocery sector increases by 19.9%, and there is a fluctuation increase/decrease in the other sectors (Impact of the Coronavirus on Digital Retail: An Analysis of 1.8 Billion Site Visits-Content square, 2020). To maintain this growing shop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…retailing marketplaces e-retailing marketplaces via identification of the five practical elements of trust, order fulfillment, website structure, excitement and interaction with analyzing their influences on the establishment of the customers' satisfaction. There are many marketing research studies and related pieces of literature confirming the linkage between trust and satisfaction, recently (Moriuchi and Takahashi, 2018;Micu et al, 2019;Trivedi and Yadav, 2020;Al-Khayyal et al, 2021). They revealed that customers' trust has a positive effect on customers' satisfaction in online environments.…”
Section: B2c Electronicmentioning
confidence: 99%
“…retailing marketplaces e-retailing marketplaces via identification of the five practical elements of trust, order fulfillment, website structure, excitement and interaction with analyzing their influences on the establishment of the customers' satisfaction. There are many marketing research studies and related pieces of literature confirming the linkage between trust and satisfaction, recently (Moriuchi and Takahashi, 2018;Micu et al, 2019;Trivedi and Yadav, 2020;Al-Khayyal et al, 2021). They revealed that customers' trust has a positive effect on customers' satisfaction in online environments.…”
Section: B2c Electronicmentioning
confidence: 99%
“…This approach mirrors JPMorgan Chase & Co.'s strategy, suggesting a typical industry trajectory towards leveraging big data to enhance profitability and customer service. However, unlike some European banks, which, as noted by Al-Khayyal et al (2020), tend to focus more heavily on risk compliance due to the region's strict regulatory environment, JPMorgan Chase & Co. demonstrates a more balanced approach between growth and compliance (Skyrius et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary technical challenges involves the complexity of integrating new data technologies with existing banking systems. This integration often requires substantial customisation and coordination to ensure that new and old systems work seamlessly together, a process that can be both timeconsuming and resource-intensive (Al-Khayyal et al, 2020;Kaisler et al, 2013). Regulatory challenges pose significant hurdles, as banks must comply with a complex web of global and regional data protection laws.…”
Section: Data Security Challenges In Bankingmentioning
confidence: 99%
“…Nowadays, E‐shopping is become a great approach among the people 1 . E‐shopping is the process of buying and selling online products such as, books, cell phones, electronic items, homely things, cloths, make up items, and also many other things 2,3 . Here, the clients telling the comments when selling these items, the comments may be positive or negative.…”
Section: Introductionmentioning
confidence: 99%
“…1 E-shopping is the process of buying and selling online products such as, books, cell phones, electronic items, homely things, cloths, make up items, and also many other things. 2,3 Here, the clients telling the comments when selling these items, the comments may be positive or negative. Therefore, the customers and the clients' opinions about the products are mentioned in the sentiment analysis (SA).…”
mentioning
confidence: 99%